Analisis Perbandingan Layanan Internet Menggunakan Apliklasi Mikhmon Dan Mikbotam - Ditty, vira; Gunawan, Erwin; Ibrahim, Adelina (Universitas Muhammadiyah Maluku Utara (Prodi Teknik Informatika), 2024)
The rapid development of the world information technology is inseparable from its supporting infrastructure. One in the field of computer networks, the development of computer networks is not only among corporates but also among IT activists who contribute to the used at the Ibu Selatan Sub-District Office is currently not property managed because there is no proxy router and server available to monitor internet services used by users In this study, the Development Life Cyele (NDLC) method was used. Through research procedures, by analzing parameters, design, implementation, monitoring, and management. At the testing stage, the configuration of the proxy, the configuration of the access point is carried out, then the internal connection is tested, then the installation of the microphone and mikbotam server is carried out. Based on the analysis in this study, the installation of the mikbotam application is easier than the mikbotam application. The mikhnon application also has features that are very complate and esay to understand. As for the mikbotam application, its features are srill in the development stage. Based on a comparative analysis of the two application, Mikhmon Server is very useful because the features in it are very complete and easy for administrators to understand for the needs of the District Office